THE SOCIAL EDUCATOR’S ABILITIES OF REFLECTION ON PROFESSIONAL EXPERIENCE IN DIFFERENT STAGES OF ACTION - Bubnys, Remigijus; Kiežaitė, Ramunė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article presents tendencies of manifestation of skills forming social educators’ abilities of reflection on professional experience and trends of their adaptability in different stages of action: reflection for action, reflection in action and reflection on action. Empirical data were collected employing a written survey method (using a structured closed type questionnaire). The data are analysed on the basis of the results of questionnaires filled in by 218 social educators. Descriptive statistics and multidimensional statistical methods (factor analysis) were applied. Research results disclose social educators’ opinion about application of skills forming reflective abilities in professional activities in different stages of action (reflection for action, reflection in action and reflection on action), when the main element of the analysis is cognitive-evaluative aspect of reflection, evaluating possibilities and conditions of applying abilities in practical activities.